Erasmus' ethnological hierarchy of peoples and races. Issue 8 (17th November 2018) - Ron, Nathan
ABSTRACT: No comprehensive research of Erasmus' ethnological mind has been published, so far. Erasmus' attitudes toward Turks and Jews were discussed analytically but not synthetically or comparatively. An attempt to widen the ethnological scope and to define and classify Erasmus' attitudes toward different non-Christian groups is presented here. Christian Europeans ( populus Christianus ) were at the top of Erasmus' echelon. Second to them were 'half-Christians', i.e. Turks, or Muslims in general. Below them were Jews, and lower in the hierarchy were black Africans ( Aethiopes ). Yet, no one was unworthy of conversion to Christianity, even barbarians of the third kind – according to Bartolomé Las Casas' sort – the most inferior barbarians, slaves by nature, as defined by Aristotle. According to Las Casas, these barbarians were too low to ask for God and were not candidates for conversion to Christianity. Erasmus' believed that Barbarians of any kind deserved Christianity without being brutally forced to accept it. Yet, in practice, converts from Judaism to Christianity were rated, even by Erasmus, as lower than Christians. This, in addition to the principle that Christian peace excludes war against the Turks, is the very essence of Erasmus' pax et concordia .